REALISASI TINDAK TUTUR LANGSUNG DALAM PRAKTIK WAWANCARA TIPE SERIOUS DISCUSSION MAHASISWA PRODI PENDIDIKAN BAHASA INDONESIA UNIVERSITAS NEGERI PADANG - Kurniati, Wahyu; Tressyalina, Tressyalina (Universitas Negeri Padang, 2019)
Abstract The purpose of this study is to describe the realization of the continuity of the educational status of Indonesian Language student speech is State University of Padang in interviews for talk show type of serious discussion. This type of research is qualitative research using descriptive method. The purpose of the descriptive is to describe, describe or depict a systematic, factual, and accurate about the facts, properties, as well as the relationship of the phenomena investigated. This research data is a fact of learning skills for survival in the realization of interviews talk show type of serious discussion and speech in the transcript of the interview performance containing acts of both direct delivered the interviewer as a student of Indonesian Language Education Status. The results of the research there is realization of the continuity of students ' skill in speech taped as much as 92.33%, with the imperative mood-imperatives as much as 3 speech by 0.74%, percentage of forms-mode interrogative-interrogative as much as 297 speech with 73.52% percentage, and declarative mode-form declarative as much as 73 speech with percentage of 18.07%. Based on the results of the study it can be concluded that the realization of the continuity of the educational status of Indonesian Language student speech is State University of Padang in skill type talk show taped for serious discussion already realized with either. Kata kunci: Relisasi, Tindak Tutur Langsung, Keterampilan Berwawancara, Gelar Wicara Tipe Serious Discussion